Vibrational fatigue and reliability of package-on-package stacked chip assembly. (October 2019) - Yang, Bing; Li, Dongbo; Yang, Haiying; Hu, Yongle; Yang, Ping
Abstract: The aim of this paper is to investigate the dynamic characteristic of package-on-package (POP) stacked chip assembly under vibration situation. The modal analysis experiment is developed with four-point fixation by force hammer excitation method, and natural frequency and modal shape are obtained. In the meantime, vibrational fatigue characteristic and reliability of POP stacked chip are investigated by applying sinusoidal excitation. We can calculate strain amplitude and duration by rain-flow counting method based on fatigue load spectrum with different excitation conditions. The results obtained by empirical formula of fatigue life can reveal the strain-lifetime law curves of POP chip with different loads. It implies that we can forecast the vibration reliability of the POP stacked chip assembly with above mentioned investigation, which provides a certain reference value for the optimization design of POP stacked chip assembly and guiding significance for the reliability design of POP stacked chip assembly.